A qui profitent les activités productives ? Analyse du cas de Cureghem - Alexandre Orban; Corentin Sanchez Trenado; Fabio Vanin (Brussels Studies)
With the growing popularity of the image of the “productive city” both in political and academic circles in Brussels, the need to keep – or even redevelop – productive activities in the city is becoming more and more widely accepted. However, while public stakeholders favour the implementation of new activities through their policies regarding productive activities and spatial planning, these transformations sometimes take place to the detriment of existing activities. Yet these productive activities are not identical in terms of location factors and their social and economic impact. This work is the result of collaboration between two research projects, and is part of a comparative and qualitative empirical approach aimed at understanding the realities which these different types of old and new activities correspond to, as well as the issues related to their continued existence or development.